Konstruksi sosial makna Tari Gandrung Seblang bagi Desa Bakungan Kecamatan Glagah Kabupaten Banyuwangi - Heri Setiawan; Sukamto Sukamto; I Dewa Putu Eskasasnanda; I Nyoman Ruja; Ratih Pramesthi (Universitas Negeri Malang, 2023)
The formulation of the problems in this study are (1) What is the history of the emergence of the Gandrung Seblang Dance tradition in Bakungan Village, Glagah District? (2) What is the form of the Gandrung Seblang Dance and the meaning contained in the Gandrung Seblang Dance tradition in Bakungan Village, Glagah District? (3) How is the Social Construction of the Gandrung Seblang Dance in Bakungan Village, Glagah District? This study used a qualitative approach with a descriptive research type. The data collection technique uses a purposive technique. The results of the study show that: (1) There are two versions of the history of the creation of the Gandrung Seblang dance in the Bakungan community. The first version states that this tradition began as a ritual to honor the services of Mbah Djoyo, a village ancestor and to express gratitude to the village guard who was willing to be transferred for the development of the village area. The second version states that the Gandrung Seblang dance arose as a result of an ancient story in which many residents of Bakungan Village experienced disease outbreaks and crop failures. The researcher suggests researching